Impact of sound irradiation on chlorella vulgaris cell metabolism - Golub, Natalia; Levtun, Igor (Eastern-European Journal of Enterprise Technologies, 2016)
The urgency of the problem is to determine the parameters of the external factor, the effect of which on Chlorella vulgaris cells increases the biosynthesis of triacylglycerols – feedstock for biodiesel production without reducing the biomass growth rate. The purpose of the paper is to determine the impact of sound irradiation on Chlorella vulgaris metabolism and biomass growth. Cultivation was carried out in the Gromov 6 medium at a temperature of 18 ± 20С. The effect of sound irradiation with frequencies of 5, 10, 15 and 20 kHz, power of 5 W/cm2 on the yield of lipids and biomass is investigated. It is shown that ultrasound irradiation with a frequency of 20 kHz increases the growth of biomass by 10% and lipids by 3 times compared to non–irradiated cells. This irradiation frequency is optimum among the studied frequencies to be used as a factor of influence for biodiesel production from Chlorella vulgaris microalgae. Irradiation with sound spectrum frequencies affects the cell metabolism towards increased biosynthesis of lipids. The specific content of the lipid fraction exceeds its content in non–irradiated cells by 1.5, 2.1 and 2 times for frequencies of 15, 10 and 5 kHz, respectively. At the same time, irradiation of microalgae cells with frequencies of 10 and 15 kHz reduces the biomass growth by 10±1 % compared to the control sample.